Family, School, and Community Partnerships for Students with Disabilities - Lo, Lusa.; Xu, Yaoying; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2019)
This book presents a collection of research-based, effective, and culturally responsive practices that are used in schools and communities to support and empower families of students with disabilities to be equal partners for schools. As the demographics of the U.S. population become increasingly diverse, the U.S. Census Bureau projects that, by 2044, more than half of the U.S. population will belong to a minority group. Currently, students from diverse backgrounds comprise over 53% of the special education student population. While their parents are the key decision makers and advocates who ensure that they receive services and support that address their individual needs, research consistently indicates that families from diverse backgrounds face many challenges that prevent them from taking on these active roles. Along with the improvements in the U.S. since the enactment of its first special education law in 1975, other parts of the world are also making changes to their special education systems in terms of responding to the diverse needs of children and students with disabilities and their families. This book also shares research-based and effective practices from other countries. The studies presented employ both qualitative and quantitative methods to investigate family-school-community partnerships.
Part I Understanding School, Family, and Community Partnerships -- 1 Partnering with Families of Young Children with Disabilities in Inclusive Settings -- 2 Empowering Families of Youth with Autism Spectrum Disorder for Success in Secondary Transition -- 3 Community Involvement: What supports are available for diverse families of students with disabilities? -- Part II Evidence-based Practices on Home-School Partnerships -- 4 Building School Level Capacity through a Problem Solving Approach to Parental Engagement in a Large Urban Setting -- 5 Partnering with Families of Students at Risk for Emotional and Behavioral Disorders -- 6 Families as Mentors: Preparing Teachers to Partner with Culturally and Linguistically Diverse Families -- Part III Evidence-based Practices on Community Involvement -- 7 A Community "Not Forgotten" -- 8 Building Capacity to Engage Culturally Diverse Families through Inter-Professional Partnerships and Training -- 9 A Community-based Approach to Providing Health and Education Supports for Students with Disabilities in Affordable Housing -- 10 Cultural Brokering Intervention for Families of Children Receiving Special Education Supports -- Part IV Evidence-based Practices in Other Parts of the World -- 11 Family Engagement Practices in Early Intervention: A Review of Three Countries -- 12 Engaging Families: A Case Study of an Elementary Inclusive School in Hong Kong -- 13 Preparing Israeli Teacher Candidates to Develop Professional/Family Partnerships.
Keywords: Educational sociology; Educational policy; Education and state; People with disabilities; Sociology of Education; Educational Policy and Politics; Disability Studies